Digital Papyrology III (De Gruyter, 2025)
The volume collects contributions about the most recent developments of the theoretical and practical concept of digital critical edition applied to Greek Papyrology, redacted by outstanding scholars involved in ground-breaking projects devoted to advanced methods of representing textual data and contextual metadata of Greek papyri in digital environments.